Transdiciplinary: Model Pengembangan Kurikulum Berorientasi Kebutuhan Individu dan Masyarakat - Alhamuddin Alhamuddin (Jurnal Pendidikan Islam Indonesia, 2017)
This paper is motivated by the diversity of problems that arise around us. However, sometimes the problem is not solved with a holistic approach, so that sometimes raises new problems. This study aimed to describe the concept of transdisiplinari developed curriculum in the schools of the future. Transdiciplinary curriculum is an approach that seeks to solve complex problems by transforming and integrating a wide range of relevant scientific viewpoints. The learning process in a transdisciplinary curriculum combines the cognitive abilities from low to high level in a manner that fosters awareness of learners against humans and humanity. The learning process developed involves aktiivitas learners to what happens in everyday life. Activities learners schools from alienated from the reality of everyday life of the community, nation and mankind.